ANALYZING THE IMPACT OF ENTERPRISE RESOURCE PLANNING (ERP) SYSTEM IMPLEMENTATION ON CONSISTENCY AND TRANSPARENCY IN FINANCIAL ACCOUNTING DISCLOSURE: AN APPLIED STUDY ON THE MIDDLE EAST INVESTMENT BANK FOR THE PERIOD 2015–2024 - Ali Bayan Talib (Scholar Express Journals, 2025)
This research purpose to analyze the impact of implementing an ERP system on the level of coherence and transparency in financial accounting announcement, through an applied study on the Middle East Investing Bank over term period from 2015 to 2024. The importance of this study stems from increasing growing role ERP systems play improved enhancing the efficiency and quality of financial coverage, especially in financial authorities where high levels of correctness and transparency in disclosure are crucial. The study working both quantitative and depictive analytical methods using the bank's promulgated financial data, in add-on to a questionnaire distributed to a sample of workforce working in the finance, IT, and internal audit branch. Data were analyzed using proper statistical tools to test hypothesis related to the ERP system's influence on the characteristics of financial unveiling. The findings specify that the implementation of the ERP system has significantly improving consistency across financial reports over distinct time periods, and has augmented transparency by provision accurate and timely information to interested party. Furthermore, the study proved a statistically considerable positive correlation between the level of system inclusion and the effectiveness of financial disclosure.
Keywords: Enterprise Resource Planning; Consistency; Transparency